Signal mining and analysis of ripretinib adverse events: a real-world pharmacovigilance analysis based on the FAERS database - Hu, Ye; Zhang, Linlin; Gong, Qineng; Huang, Lei; Yin, Cunlin; Miao, Yang; Wu, Hui (Frontiers in Pharmacology, 2025)
BackgroundRipretinib is a tyrosine kinase inhibitor indicated for the treatment of adult patients with advanced gastrointestinal stromal tumors (GISTs) who have previously received treatment with at least three kinase inhibitors. The objective of this study was to evaluate adverse events(AEs) associated with ripretinib using data from the FDA Adverse Event Reporting System (FAERS) database.MethodsIndividual case safety reports (ICSRs) related to of ripretinib from 2020 Q2 to 2024 Q2 were extracted from the FAERS database. This study used the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) for disproportionality analysis. In addition, this research also performed a descriptive analysis of the time-to-onset (TTO) of AEs related to ripretinib.ResultsA total of 3,513 ICSRs with ripretinib as the primary suspect (PS) were retrieved from the FAERS database. At the preferred term(PT) level, this study detected 116 positive AEs. Common AEs included alopecia, constipation, muscle spasms, dry skin, decreased appetite. Notably, unexpected AEs such as pleural mass, blood magnesium abnormal, blood potassium abnormal, hepatic lesion, and liver abscess were also observed. The median time to onset of ripretinib-related AEs was 102 days (29–254 days), with the majority of AEs occurring during the first month of treatment.ConclusionThis study identified some known AEs associated with ripretinib and discovered unexpected AEs, providing preliminary insights into its safety in the real world. This information is valuable for clinical monitoring and the safe use of ripretinib.